1985
DOI: 10.1007/bf00662429
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and physicochemical characterization of mitochondrial DNA from cultured cells ofPetunia hybrida

Abstract: Mitochondrial DNA ofPetunia hybrida was purified from cell suspension cultures. Up to 50% of the DNA could be isolated as supercoiled DNA molecules by CsCl-ethidium bromide density gradient centrifugation. The DNA purified from DNase-treated mitochondria bands at a single buoyant density of 1.760 gcm(-3) in neutral density gradients and runs on agarose gels as a single band with an apparent molecular weight exceeding 30 megadaltons (Md). Summing of the restriction endonuclease fragment lengths indicates a mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Currently, it is still uncertain which mitochondrially encoded protein is responsible for the developmental abnormalities in the ems petunia anthers. Deviations in mitochondrial DNA arrangement are found in organelles purified from suspension cultured cells (KOOL et al, 1985;BOESHORE et al, 1985). Certainly, a ems-specific variation in gene expression may be expressed in these vegetative cells, as well as in reproductive tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is still uncertain which mitochondrially encoded protein is responsible for the developmental abnormalities in the ems petunia anthers. Deviations in mitochondrial DNA arrangement are found in organelles purified from suspension cultured cells (KOOL et al, 1985;BOESHORE et al, 1985). Certainly, a ems-specific variation in gene expression may be expressed in these vegetative cells, as well as in reproductive tissues.…”
Section: Resultsmentioning
confidence: 99%
“…In ems Petunia hybrida, KOOL et al (1985) demonstrated that the ems plasmatype is correlated with changes in mitochondrial DNA composition and its translational products. The ems-associated DNA arrangement and a homologous mitochondrial DNA region from a male fertile line are subjected to sequence and transcription analysis (BOESHORE et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Isolation, characterization and sequencing of P. hybrida mtDNA potential replication origin regions. In order to isolate P. hybrida mtDNA replication origins, purified P. hybrida mtDNA (Kool et al 1985) was digested with BamHI or BamHI/EeoRI, ligated in the appropriate linearized yeast-E, coli shuttle vector YIp5 and analyzed for autonomous replication in yeast by transforming the mtDNA bank to the ura3 yeast strain DLlc~. Transformants were selected for uracil-independent growth; because the YIp5 vector itself cannot replicate in yeast, the observed high frequency transformation should be the result of recombinant plasmids carrying mtDNA fragments which promote autonomous replication in yeast (so-called mtDNA ARS fragments).…”
Section: Methodsmentioning
confidence: 99%
“…The P. hybrida liquid cell suspenison culture AK5000 was grown as described (Kool et al (1985) with the exception that the homogenization buffer H consisted of 330 mM sorbitol, 30 mM Tris-HC1 pH 8.0, 10 mM NaC1, 10 mM MgC12 and 2 mM 2-mercaptoethanol. The final mitochondrial pellet was resuspended in 1.5 ml of H-buffer and lysed by adding two volumes of lysis buffer L [0.75 M NaC1, 50 mM Tris-HC1 pH 8.0, 2 mM DTT, 20% (v/v) glycerol, 50 p.g/ml PMSF and 50 ~tg/ml TOSF; the latter two components were dissolved at 10 mg/ml in iso-propanol].…”
Section: Methodsmentioning
confidence: 99%
“…When male sterility is governed by cytoplasmic factors (plasmagenes), in association with nuclear gene (s), it has been termed as cytoplasmic male sterility (CMS). Biochemical studies indicate that the CMS trait is encoded by the mitochondrial genome (Levings 1983, Kool et al 1985, Mann et al 1989.…”
mentioning
confidence: 99%